Challenges and opportunities in harnessing soil disease suppressiveness for sustainable pasture production. (April 2016) - Dignam, Bryony E.A.; O'Callaghan, Maureen; Condron, Leo M.; Raaijmakers, Jos M.; Kowalchuk, George A.; Wakelin, Steven A.
Abstract: Grasslands are an important source of biodiversity, providing a range of essential ecosystem services such as ensuring water quality and soil carbon storage. An increasing proportion of grasslands are used for pastoral agriculture, supporting production of domestic livestock. Pasture productivity is significantly affected by soil-borne microbial pathogens. Reducing the impact of soil-borne diseases in pastures is challenging given the complexity of interactions within the soil/rhizosphere microbiome and the diverse impacts of vegetation, land management, soil conditions and climate. Furthermore, there are fewer opportunities to control plant pathogens in pastures compared to arable cropping systems. The greater diversity of vegetation leads to the development of more diverse and less well characterized pathogen complexes, and the application of agrochemicals for control of soil-borne diseases is economically prohibitive and ecologically undesirable. Soil-borne plant pathogens can be suppressed through the general activity of the total soil microbiota acting in competition with the pathogenic microbiota, or by increases in the abundance and activity of specific microbes or microbial consortia that are antagonistic against selected pathogens. The development of strategies that enhance disease suppressiveness in pastures will depend not only on phylogenetic assessment of microbial communities, but also on a mechanistic understanding of the functional potential and properties (i.e. disease suppressive traits) of the soil microbiome. Collectively, this fundamental knowledge will be essential to identify the factors driving the emergence of desired disease suppressive microorganisms and traits. To understand and predict disease suppressive functionality, the spatial and temporal variability of the soil and plant-associated microbial populations and their activities must be taken into account. A systems-based approach is therefore required to identify the obstacles and opportunities related to controlling plant pathogens in pasture systems. Such an integrated approach should incorporate a "microbial" perspective to examine traits, drivers and activities of soil-borne microbes, while utilizing emerging tools in ecological genomics, as well as computational, statistical and modelling approaches that also accommodate the chemical and physical complexity of soil ecosystems. Highlights: Soil-borne microbial pathogens substantially constrain productivity in pastures. Complex agricultural systems present unique challenges for disease control. Soil disease suppressiveness has a potential role in sustainable pasture production. Processes leading to enhanced disease suppression in pasture require investigation. A systems-based approach is required to manage the suppressive microbiome